2013
DOI: 10.1038/hdy.2013.58
|View full text |Cite
|
Sign up to set email alerts
|

Testing the consistency of connectivity patterns for a widely dispersing marine species

Abstract: Connectivity is widely recognized as an important component in developing effective management and conservation strategies. Although managers are generally most interested in demographic, rather than genetic connectivity, new analytic approaches are able to provide estimates of both demographic and genetic connectivity measures from genetic data. Combining such genetic data with mathematical models represents a powerful approach for accurately determining patterns of population connectivity. Here, we use micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 76 publications
2
46
0
Order By: Relevance
“…As shown by Thomas & Bell (), the persistent larval sources/sinks that we identified have the potential to impact upon the genetic connectivity of local subpopulations. For instance, the genetic homogeneity found among the sea bream ( Diplodus sargus ) populations of the Italian, French and Spanish coasts (Lenfant & Planes, ) could be related to the efficient gene flows occurring among those source areas.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…As shown by Thomas & Bell (), the persistent larval sources/sinks that we identified have the potential to impact upon the genetic connectivity of local subpopulations. For instance, the genetic homogeneity found among the sea bream ( Diplodus sargus ) populations of the Italian, French and Spanish coasts (Lenfant & Planes, ) could be related to the efficient gene flows occurring among those source areas.…”
Section: Discussionmentioning
confidence: 59%
“…Our results, and more generally the tunable modelling framework proposed here, should allow (1) formal testing of the effects of specific oceanographic processes on population genetics by integrating the most relevant biological traits for a group of species into this general framework, and (2) targeting of sub-regions with dissimilar connectivity behaviours as predicted here, whose effects on connectivity in relation to species distributions and life-history traits could be evaluated. As shown by Thomas & Bell (2013), the persistent larval sources/sinks that we identified have the potential to impact upon the genetic connectivity of local subpopulations. For instance, the genetic homogeneity found among the sea bream (Diplodus sargus) populations of the Italian, French and Spanish coasts (Lenfant & Planes, 1996) could be related to the efficient gene flows occurring among those source areas.…”
Section: Unifying Hydrodynamic and Genetic Connectivitymentioning
confidence: 83%
“…Currents have been well documented to be a major force influencing gene flow in the marine environment [20,24,30,80,81]. Variable ocean currents and bathymetric complexities can work synergistically to produce fine-scale source-sink dynamics that isolate local populations and produce high levels of genetic divergence, particularly across island archipelagos that are made up of a mosaic of reefs [37].…”
Section: Discussionmentioning
confidence: 99%
“…While S. verreauxi are yet to be assessed with high resolution genetic markers, SNPs recently confirmed a trans-Tasman genetic break in the co-distributed, closely related, commercially important Southern Rock Lobster, Jasus edwardsii (Villacorta-Rath et al 2016). Oceanographic models indicate that trans-Tasman gene flow for both species of lobster is possible due to their long PLDs (Chiswell et al 2003); microsatellite studies have indicated that for J. edwardsii, trans-Tasman gene flow occurs at levels low enough to maintain genetic structure (Thomas and Bell 2013). As S. verreauxi and J. edwardsii have many similar life-history characteristics, such as long pelagic larval durations, high fecundity and restricted breeding times (Table 1), we could expect the subdivision detected for J. edwardsii to be mirrored in S. verreauxi populations.…”
Section: Introductionmentioning
confidence: 99%